El Salvador Financial Sector Assessment Program Update : Capital Market Development - International Monetary Fund (Washington, DC, 2017)
The capital markets in Salvador are small and relatively underdeveloped, and have played a very limited role in the economy. On average, institutional investors invest less than 10 percent of their total assets in capital market instruments. In 2009, there were only five new issuances of corporate bonds and three in the case of equity. Banks and pension funds are the main institutional investors. The current market architecture and the natural monopoly it grants to the exchange hamper market development and prevent the modernization of the regulatory framework. There is an urgent need to overhaul of the regulatory framework to promote sound market development in the short-to-medium term. The regulatory framework should guarantee a level playing field between bonds and bank deposits, which should be reflected in the investment guidelines for institutional investors. The exchange should reposition itself to become more competitive and strategic at the local and regional level. The investment funds law should be finally approved to broaden and diversify the investor base. The importance of this reform is paramount as the current reliance on just two main institutional investors (banks and pension funds), with investment limitations (35 percent each per issue), creates a major limitation for new issuances. In the medium -to long- run, it is recommended to explore gradually integrating the individual markets at the regional level. This paper is divided into following four parts: part one gives current market situation; part two gives regulatory and supervisory framework; part three gives recommendations; and part four is reference section.